Analysis on the Amplification Effect of Diode Rectifier Unbalance Input Current - LIU Fei; ZHOU Ben; WANG Ting (Kongzhi Yu Xinxi Jishu)
It is hard to design the filter of diode rectifier due to the input current amplification effect. In order to offer more precise guidance to filter parameter design, this paper brings about this amplification phenomenon by an analysis method which is based on switch function and equivalent model appling symmetrical component to deduce. Without considering the overlap,the relationship between current unbalance and voltage unbalance is derived, which reveal that the resonance frequency of the LC filter directly affects the amplification effect.The correctness and effectiveness of the conclusions and analysis methods are verified by Matlab/Simulink simulation.